The main causes and corresponding solutions of skin pigmentation in the body - Benyue Li; Huaqian Mei; Zhishan Zhou; Jie Yang; Yexiang Zhang; Fengwei Qi (Journal of Dermatologic Science and Cosmetic Technology)
The skin's normal color is primarily determined by the quantity and distribution of pigment, the level of hemoglobin in the skin's blood vessels, and various optical factors. Additionally, mechanical damage from clothing renders certain areas of the body more susceptible to hyperpigmentation, such as the elbows and knees. According to research, various factors such as gender and weight have been found to influence skin color. The mechanism of body skin pigmentation has been extensively studied with a particular focus on melanogenesis and related signaling pathways. Therefore, this article primarily focuses on elucidating the mechanisms governing body pigmentation while discussing strategies for managing skin whitening, encompassing influential factors and whitening methods.